DIHIDUPKANNYA KEMBALI PATEN NOMOR IDP000028054 BERDASARKAN UNDANG-UNDANG PATEN: Revival of Patent Number IDP000028054 Under the Patent Law - y, Anastasya; Nugrahani, Rr.Aline Gratika (AMICUS CURIAE, 2024)
A right to a Patent may be removed for certain reasons. In the case of a Patent IDP000028054 in the form of a U Profile is abolished because the owner of the Patent is considered negligent in making payment of the annual fee of the Patent. So the issue that arises is whether the judge's reasons and considerations in the deletion of the U Profile Patent are in accordance with the Patent Law and whether the judge's consideration of the revival of the U Profile Patent that has been abolished is in accordance with Article 141 of the Patent Law. In order to answer this problem, normative research is carried out which is descriptive analysis sourced from secondary data taken through document and literature studies. Data processing is carried out qualitatively, then conclusion making is carried out using deductive logic methods.As per the analysis of this ruling, it is known that the deletion of the U Profile Patent is unlike the applicable provisions under the Patent Law and the judge's consideration relating to the revival of the U Profile Patent is in accordance with the Patent Law